FENOMENA LITERASI MATEMATIKA SISWA DI INDONESIA BERDASARKAN HASIL PISA - Anis Munfarikhatin; Sadrack Luden Pagiling; Irmawaty Natsir (Jurnal Pembelajaran dan Pengembangan Matematika, 2022)
ABSTRACT This study aims to examine the phenomenon of research on students' mathematical literacy in Indonesia after the 2018 PISA assessment. The research method uses a literature study from 27 articles published from 2019 to 2021 taken from indexed journals of national reputation. The data analysis technique used tabulation and classification methods based on the year of publication, type of research, research methods, instruments, and research findings. The results show the percentage of articles published in 2020 (30%), in 2020 (48%) and in 2021 (22%). The type of research used was qualitative (48%), quantitative (33%), developmental (7%), survey (4%) and literature study (7%). The research method applied is descriptive (52%), quasi-experimental (26%), pre-experimental (4%), exposed fact (7%), Borg and Gall development (4%), Tessmer development (4%), and correlation (4%). The research is more dominant in discussing the profile of mathematical literacy abilities, the influence of learning models on mathematical literacy skills, and the development of learning tools in the form of modules, the rest describes the results of literature studies on mathematical literacy. Keywords: Mathematics literacy; PISA; study of literature ABSTRAK Penelitian ini bertujuan mengkaji fenomena penelitian mengenai literasi matematika siswa di Indonesia setelah penilaian PISA tahun 2018. Metode penelitian menggunakan studi literatur dari 27 artikel yang terbit mulai tahun 2019 sampai tahun 2021 yang diambil dari jurnal terindeks bereputasi nasional. Teknik analisis data menggunakan metode tabulasi dan klasifikasi berdasarkan tahun terbit, jenis penelitian, metode penelitian, instrumen, dan temuan penelitian. Hasil penelitian menunjukkan persentase artikel terbit di tahun 2020 (30%), tahun 2020 (48%) dan tahun 2021 (22%). Jenis penelitian yang digunakan kualitatif (48%), kuantitatif (33%), pengembangan (7%), survey (4%) dan studi literatur (7%). Metode penelitian yang diterapkan adalah deskriptif (52%), kuasi eksperimen (26%), pre eksperimen (4%), ekspose fakto (7%), pengembangan Borg and Gall (4%), pengembangan Tessmer (4%), dan korelasi (4%). Penelitian lebih dominan membahas mengenai profil kemampuan literasi matematika, pengaruh model pembelajaran terhadap kemampuan literasi matematika, dan pengembangan perangkat pembelajaran berupa modul, selebihnya memaparkan hasil studi literatur tentang literasi matematika. Kata Kunci: Literasi matematika; PISA; studi literatur